Dietary Niche Partitioning of Euphaea formosa and Matrona cyanoptera (Odonata: Zygoptera) on the Basis of DNA Barcoding of Larval Feces. Issue 1 (18th July 2016) - Cheng, Yun-Chieh; Lin, Chung-Ping
Abstract: Odonate larvae are commonly considered opportunistic general predators in freshwater ecosystems. However, the dietary breadth of most odonate larvae in forest streams is still poorly documented. We characterized the prey species and estimated the level of dietary niche overlap of two damselflies, Euphaea formosa Hagen 1869 and Matrona cyanoptera Hämäläinen and Yeh, 2000 in a forest stream of central Taiwan on the basis of DNA barcoding of larval feces. A collection of 23 successfully identified cytochrome c oxidase 1 ( CO1 ) barcoding sequences suggested that the mayflies (Ephemeroptera), caddisflies (Trichoptera), and midges (Diptera) comprise the majority (43%, 6/14) of prey species consumed by E. formosa larvae, whereas the identified prey for M. cyanoptera were mainly zooplankton (56%, 5/9). Statistical analysis of dietary overlap indicated that these two species occupy different dietary niches (Pianka's index = 0.219). DNA barcoding analysis of damselfly larval feces was effective in detecting less sclerotized prey such as vertebrates (fish and frog) and small zooplankton. However, a moderately successful rate (<70%) of PCR amplification by universal CO1 primers and a low percentage (<60%) of identifiable sequences in public databases indicate the limitations of naive DNA barcoding in fecal analysis.